UiTM Perak Branch received a work visit from Vice-Chancellor of UiTM / Unit Komunikasi Korporat - UiTM Cawangan Perak, Unit Komunikasi Korporat (Universiti Teknologi MARA, Perak, 2022)
On 22nd February 2022, UiTM Perak Branch has recorded history with the visit of the new Vice-Chancellorof UiTM, YBhg. Prof. Datuk Ts Dr Hajah Roziah Mohd Janor to Seri Iskandar and Tapah campuses. This isher inaugural visit to UiTM Perak Branch and the Rector, all management executives, academic and non-academic staff and students welcomed Vice-Chancellor ceremonially.